2014
DOI: 10.1586/14737175.2014.927735
|View full text |Cite
|
Sign up to set email alerts
|

The possible long-term effects of early-life circadian rhythm disturbance on social behavior

Abstract: Sleep loss impairs brain function. As late sleep onset can reduce sleep, this sleep/circadian rhythm disturbance may cause brain impairment. Specific data on the long-term effects of sleep/circadian rhythm disturbance on subsequent brain function are lacking. Japan, a sleep-deprived society from infancy to adulthood, provides an ideal platform to investigate the association of these disturbances in early life with subsequent functioning. In this article, several current problematic behaviors among youth in Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…A relationship of insomnia with obesity and metabolic syndrome has been reported (4). The reason for this was increased activity in the amygdala together with decreased activity in the frontal cortex and insular cortex (5).…”
Section: Statistics For Night Shifts and Do Night Shifts Lead To Healmentioning
confidence: 97%
See 2 more Smart Citations
“…A relationship of insomnia with obesity and metabolic syndrome has been reported (4). The reason for this was increased activity in the amygdala together with decreased activity in the frontal cortex and insular cortex (5).…”
Section: Statistics For Night Shifts and Do Night Shifts Lead To Healmentioning
confidence: 97%
“…Kohyama has suggested that the reason why Japan and Korea have the highest suicide rates might originate from the fact that these are countries where the people sleep less or they do not like to sleep (4). When compared with people who sleep for 6-8 h a day, the suicide rate is 3.5 (HR: 2.0-6.1) times higher in people who sleep for 0-4 h a day, and sleeping for less than 6 h is a risk factor for suicide (6).…”
Section: Statistics For Night Shifts and Do Night Shifts Lead To Healmentioning
confidence: 99%
See 1 more Smart Citation
“…Many risk factors have been associated with suicide [7][8][9][10], such as psychiatric disorders (depression being probably the most important risk factor [1]), impulsive or aggressive behaviour, family history of suicide, loss of a close friend or relative, physical or sexual abuse, lack of a support network, or sleep disturbances, especially with a chronic evolution [1,11]. Concerning this last factor, nightmares and insomnia have been consistently reported to increase the risk of suicidal behaviours, even after adjusting for depression severity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For children and adolescents, it was found that: a) the sleep habits acquired in childhood persist through adulthood and largely influence sleep patterns later in life [11,16]; b) adolescents have a biological tendency to suffer circadian rhythm alterations characterized by a sleep phase delay, tending to sleep later, but still have to wake up early due to school or family obligations [5,[25][26][27][28]. This promotes a circadian desynchrony and a state of sleep deprivation, if good habits about bedtime and activities performed before sleep are not induced at home; c) they also are a risk group for suicide, likely due to a proneness for emotional instability and impulsive behaviours, with a less developed ability to correctly evaluate the long term consequences of their behaviours [14].…”
Section: Introductionmentioning
confidence: 99%